1984
DOI: 10.1007/bf00848228
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies of the influence of prolactin on tail regeneration in the adult newtNotophthalmus viridescens

Abstract: In vitro experiments were carried out to determine the effects of prolactin, and prolactin in combination with other hormones on the regeneration of adult newt tail blastemata. A total of 271 blastemata were explanted 13 days postamputation and were organ cultured for 96 h at 20 (±1)°C. Treatment with prolactin alone resulted in an increase in the blastema cell density of the tail regenerates. Cell accumulation and cell alignment were observed ventral to the reconstituted spinal cord. Prolactin and thyroxine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Rhythmicity of melatonin and serotonin secretion may influence regeneration by modulating the secretion of prolactin [ 88 ]. Studies have shown that prolactin significantly increases regeneration in newt forelimbs and newt and lizard tails [ 51 , 52 , 94 , 95 ]. Thus, an increase in regeneration occurring under conditions of constant light may be due to high levels of serotonin, which stimulates the release of prolactin [ 44 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rhythmicity of melatonin and serotonin secretion may influence regeneration by modulating the secretion of prolactin [ 88 ]. Studies have shown that prolactin significantly increases regeneration in newt forelimbs and newt and lizard tails [ 51 , 52 , 94 , 95 ]. Thus, an increase in regeneration occurring under conditions of constant light may be due to high levels of serotonin, which stimulates the release of prolactin [ 44 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the proliferation and differentiation of blastema cells is under hormonal control. In experiments with the cultivation of regenerating tail blastemas in a medium with individual hormones such as prolactin, insulin, thyroxine, hydrocortisone, and their combinations, two multidirectional hormonal effects regulating the course of regeneration were identified [184]. Prolactin and insulin promoted intensive proliferation of blastema cells but inhibited differentiation; thyroxine, on the other hand, enhanced chondrogenesis.…”
Section: Molecular Regulators Of Tail Regeneration In Salamanders 41 ...mentioning
confidence: 99%
“…The rate of blastema production and growth is a determinant of the overall observable rate of early regeneration in fins and limbs and may also be reflected in the rate of regeneration of the full structure in some instances. In these newts, serotonin-stimulated prolactin release promotes increased cell density at the blastema site, which may be due to increased cellular proliferation, decreased cell death, and/or increased blastema cell recruitment, and subsequently accelerates regeneration rate 10 , 40 , 41 . However, the precise molecular mechanism of prolactin action in the context of regeneration remains unknown.…”
Section: Eternal Cuesmentioning
confidence: 99%